EFFORTS TO IMPROVE ACADEMIC SERVICE GOVERNANCE THROUGH OPTIMIZATION OF INFORMATION TECHNOLOGY AT GORONTALO STATE UNIVERSITY - Badjuka, Alexander H.; Aneta, Asna (Universitas Negeri Gorontalo, 2022)
In maintaining the existence of the State University of Gorontalo, a quality higher education management system is needed to be able to adapt to the dynamics of change.Â Good governance of the State University of Gorontalo is a condition that ensures a synergistic process between internal elements and the support of external parties, as well as mutual control carried out by related components within an organization.Â This study aims to analyze what efforts can be made to improve the governance of academic services through optimizing information technology at the State University of Gorontalo. This research method is qualitative. Data collection was carried out through a literature study by tracing the sources of previously written writings obtained from various sources, journals, documentation books, the internet, and libraries. The results of the study show that efforts that can be made to improve the governance of academic services at the State University of Gorontalo are through structuring the management of functional aspects consisting of (1) Management of the academic service system centered on a curriculum that is adapted to the national curriculum, structuring the educational process cycle starting from student admissions. until graduation, and the arrangement of the Teaching and Learning Process; (2) The development and management of human resources starts from determining the number, quality, and effective teaching staff and education staff in accordance with the needs of higher education institutions to arranging pensions, dismissals, and severance pay for human resources; (3) The management of the financial performance system, namely the process of managing funds from receipt to use of the budget, can be properly accounted for based on applicable regulations; and (4) Improving facilities and infrastructure services by preparing all equipment/materials for the smooth implementation of the educational process. includes planning, procurement, storage of equipment items, maintenance, and removal.